Holistic Education in Greta Gerwig’s “Little Women” - Alfianita Pramudyani; Restu Arini (Siliwangi University, 2022)
Holistic education is an approach that appreciates all the aspects of human potencies. As the first teachers of the children, parents are the ideal models who should grow the children holistically. This study aims to discuss the portrayal of holistic education in Little Women, a movie by Greta Gerwig. The main focus of this study is 1) underlining how holistic education became the standard in raising the four daughters in the novel, and 2) the impact of holistic parenting towards their adulthood. To solve the problem, a library study and in-depth analysis are taken and a descriptive-qualitative method is used. The study reveals that 1) within the childhood to adolescence, the parents raise their daughters by fulfilling all aspects of children development – not only their physical but also the four quotients in holistic education: intellectual (IQ), mental or spiritual (SQ), emotional (EQ), and adversity (AQ) and also social ability; thus, 2) the implementation of holistic education gives a very positive impact towards the daughter; makes the daughters capable of facing the demands and challenges of their life especially when they cope problems appears in their career, society and marriage life.